Prediksi Penggunaan Air Bersih Menggunakan Metode K-Nearest Neighbour Di PDAM Tirta Musi Kantor Unit KM IV Palembang - KEMAS MUHAMMAD WAHYU HIDAYAT, KEMAS MUHAMMAD WAHYU HIDAYAT (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The water distribution allocation service by PDAM Tirta Musi, KM IV Unit Office, Palembang, has given rise to a new problem where PDAM Tirta Musi, KM IV Unit Office, has difficulty in meeting clean water needs. One of the efforts that PDAM has made to overcome this is by trying to organize water rotation. clean in every area. The solution taken actually gave rise to a new problem, namely that there were several areas that temporarily did not receive a clean water supply, giving rise to demands from the community that clean water must be distributed evenly in every area where the community lives. Based on this problem, it is necessary to design a water demand prediction application whose aim is to help PDAM Tirta Musi KM IV Palembang Unit Office to allocate water distribution to customers so that there is no shortage or waste. This research was conducted using the K-Nearest Neighbor development method. The application for predicting clean water usage at PDAM Tirta Musi Unit KM IV Palembang Office was built on a web basis to help predict the level of water usage at PDAM Tirta Musi Unit KM IV Palembang Office and can help distribute water supplies evenly in Palembang City. Keywords— complexity of PDAM TIRTA MUSI, K-Nearest Neighbor, water distribution